An Isolated fallopian tube torsion : A rare cause of acute abdomen: isolated fall plush tube torsion - Asefa, Eyob; Kedida, Bezza (Ethiopian Journal of Reproductive Health, 2025)
Isolated fallopian tube torsion (IFTT) is the rotation of fallopian tube along its long axis, which results in obliteration of blood supply while ovary’s blood supply and lymphatic drainage remain unaffected. The prevalence of IFTT was estimated to be only 1 in 1,500,000 but is believed to be rarer. Although the pathophysiology of IFTT is not well known, there are well-defined risk factors for the disease. It most commonly affects the right side of fallopian tube rather than left side. Clinical presentation: A 20-years-old woman presented with acute severe lower abdominal pain, vomiting and lower back pain. She had a urinary complaint of 3 days duration. Pertinent finding Physical examination: Vital sign: PR= 110 bpm, temp= 38 c°. On abdominal examination, there is significant tenderness on the lower abdomen on deep palpation. GUS: there is no abnormal vaginal discharge. On vaginal digital examination, there is tenderness on the right side of the pelvis. Discussion: Isolated fallopian tube torsion (IFTT) is an extremely rare disease entity. Predisposing factors are classified as intrinsic and extrinsic factors. It occurs in reproductive age groups. It is a rare cause of acute abdomen in reproductive age group. This case presented with severe acute abdominal pain, vomiting, and urinary symptoms. On physical examination, she was febrile and had abdominal tenderness. Ultrasound shows a dilated fallopian tube and pelvic collection. These findings are nonspecific which leads to acute PID diagnosis. IFTT was diagnosed intraoperatively after 48 hours of antibiotics treatment for PID, which did not respond. Diagnosis of IFTT remained challenging as it presents with nonspecific clinical features. Conclusion: IFTT remained difficult to diagnose early due to nonspecific clinical presentation. Acute PID is one of the top differential diagnoses in sexually active patients. To improve early diagnosis of IFTT, advanced medical imaging, like MRI, is advised. The less invasive surgical approach is the gold standard treatment. Salvaging the fallopian tube is a priority if the tube is not gangrenous. Key words Isolated fallopian tube torsion, pelvic inflammatory disease, acute abdomen